Censored: how European „hate speech“ laws are threatening freedom of speech - Coleman, Paul B. (Kairos Publications, 2016)
Despite the importance of freedom of speech and robust public debate, the nations of Europe have all adopted criminal laws against so-called “hate speech.” In Germany, for example, committing an insult is a criminal offence and in Poland offending religious feelings carries a two year prison sentence. In Cyprus, anyone who promotes feelings of ill will may be committing a crime, while in Sweden anyone who expresses contempt towards a group of persons may be imprisoned. Across Europe, such laws are readily being used. Ministers of religion have been arrested for preaching sermons from the Bible, journalists have been routinely fined, and even private conversations between citizens have resulted in criminal investigations. Yet remarkably, there appears to be almost unwavering support for “hate speech” laws among major European institutions and many non-governmental organizations.